2006
DOI: 10.1083/jcb.200602086
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for tetraspanin functions as revealed by the cryo-EM structure of uroplakin complexes at 6-Å resolution

Abstract: Tetraspanin uroplakins (UPs) Ia and Ib, together with their single-spanning transmembrane protein partners UP II and IIIa, form a unique crystalline 2D array of 16-nm particles covering almost the entire urothelial surface. A 6 Å–resolution cryo-EM structure of the UP particle revealed that the UP tetraspanins have a rod-shaped structure consisting of four closely packed transmembrane helices that extend into the extracellular loops, capped by a disulfide-stabilized head domain. The UP tetraspanins form the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 72 publications
6
120
1
1
Order By: Relevance
“…One is located in the LEL, and the second one is located in the TM2/ TM3 region, which is mainly composed of transmembrane regions (20). In addition, the analysis of urothelial plaques, hexagonally packed 16-nm uroplakin particles that cover the urothelial apical surface, by cryo-electron microscopy at 6 Å resolution revealed that the non-tetraspanin uroplakins were in contact with both the LEL and the transmembrane domains (most likely TM3 and/or TM4) of their tetraspanin partners (41).…”
Section: Discussionmentioning
confidence: 99%
“…One is located in the LEL, and the second one is located in the TM2/ TM3 region, which is mainly composed of transmembrane regions (20). In addition, the analysis of urothelial plaques, hexagonally packed 16-nm uroplakin particles that cover the urothelial apical surface, by cryo-electron microscopy at 6 Å resolution revealed that the non-tetraspanin uroplakins were in contact with both the LEL and the transmembrane domains (most likely TM3 and/or TM4) of their tetraspanin partners (41).…”
Section: Discussionmentioning
confidence: 99%
“…21 However, acting through this type of interaction was reported by only one group. The extracellular part of tetraspanins protrudes B5 nm from the cell membrane 55 which, together with much 'taller' (B20 nm) associated integrins, makes direct homophilic binding between CD151's on neighboring cells physically rather unlikely. Fluorescence Resonance Energy Transfer (FRET) analysis showed that CD151 and a3b1 integrin associated at the front and retracting rear of polarized migrating breast carcinoma cells in 2D and 3D matrices.…”
Section: Modulation Of Integrin-ligand Interactionsmentioning
confidence: 99%
“…crystallography is not an "all or nothing" approach, and structural information can be extracted even from poorly ordered 2D crystals. Electron crystallography has thus contributed structural information of many membrane proteins in the 10Å range, providing valuable information on the arrangement of the transmembrane α-helices in these proteins (e.g., [14][15][16]). …”
Section: A Game Of Numbers the Number Of Solved Structuresmentioning
confidence: 99%